2020
DOI: 10.21037/tlcr-20-546
|View full text |Cite
|
Sign up to set email alerts
|

Integrating immune checkpoint inhibitors and targeted therapies in the treatment of early stage non-small cell lung cancer: a narrative review

Abstract: Prognosis of early stage non-small cell lung cancer (eNSCLC) is poor even when treated radically with surgery and (neo)adjuvant chemotherapy (Cht). The discovery of tyrosine kinase inhibitors (TKIs) for oncogene addicted NSCLC and immune checkpoint inhibitors (ICIs) have revolutionised the therapeutic paradigm and improved survival of advanced NSCLC. The unprecedented impact of these drugs has shifted the focus of investigation to early stage disease aiming at improving cure. In this context, several single ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 82 publications
0
12
0
Order By: Relevance
“…LUAD is characterized by a high degree of heterogeneity, and studies have demonstrated that a variety of genetic mutations and epigenetic changes drive the development and progression of LUAD, including gene fusion, major chromosomal events, single nucleotide changes (SNVs) and copy number alterations (CNAs) (36,37). In recent years, with the in-depth understanding of the changes in the molecular mechanism of LUAD, many molecular targeted drugs for the precise treatment of LUAD have been developed, such as tyrosine kinase inhibitors (TLIs) of epidermal growth factor receptor (EGFR) and PDL1/PDL inhibitors (38,39), which bring hope to LUAD patients. However, these mutations are not ubiquitous in all LUAD patients, and existing targeted drugs are only effective in some patients, and even some patients develop resistance and relapse during treatment.…”
Section: Discussionmentioning
confidence: 99%
“…LUAD is characterized by a high degree of heterogeneity, and studies have demonstrated that a variety of genetic mutations and epigenetic changes drive the development and progression of LUAD, including gene fusion, major chromosomal events, single nucleotide changes (SNVs) and copy number alterations (CNAs) (36,37). In recent years, with the in-depth understanding of the changes in the molecular mechanism of LUAD, many molecular targeted drugs for the precise treatment of LUAD have been developed, such as tyrosine kinase inhibitors (TLIs) of epidermal growth factor receptor (EGFR) and PDL1/PDL inhibitors (38,39), which bring hope to LUAD patients. However, these mutations are not ubiquitous in all LUAD patients, and existing targeted drugs are only effective in some patients, and even some patients develop resistance and relapse during treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The most common histology is non-small cell lung cancers (NSCLC), which accounts for nearly 85% of cases [2], and the vast majority of NSCLC patients are found in in the stage of advanced inoperable [3] since early stage tumor development is usually asymptomatic [4]. The prognosis of early NSCLC is poor even if it is treated by surgery and neoadjuvant chemotherapy [5]. Up to 70% of NSCLC patients develop central nervous system metastases during the course of their disease [6].…”
Section: Introductionmentioning
confidence: 99%
“…Different clinical trials have been performed with the aim to evaluate the efficacy of TKIs targeting activating mutations in EGFR in the neoadjuvant and also in the adjuvant setting [18][19][20]. Briefly, these trials have used or use inhibitors of the first, second, and third TKI generation [19,21].…”
Section: Short Overview Of Studies Concerning the Use Of Egfr Tkis In Early Stage Nsclc In Neoadjuvant And Adjuvant Settingmentioning
confidence: 99%